1998
DOI: 10.1159/000054340
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic Lesions Induced by Monosodium Glutamate Result in Increased Adenopituitary Proopiomelanocortin Gene Expression and Decreased Corticosterone Clearance in Rats

Abstract: Hypothalamic-pituitary-adrenocortical function in rats with brain lesions induced by neonatal monosodium glutamate (MSG) treatment (4 mg/g, 5 administrations, i.p.) was evaluated in the present study. Using in situ hybridization we found increased proopiomelanocortin (POMC) mRNA levels in the adenopituitary and normal corticotropin-releasing hormone mRNA levels in the hypothalamic paraventricular nucleus in MSG-treated rats. The total content of pituitary adrenocorticotropin (ACTH) was not changed, while pitui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…21 Conversely, circulating FB concentrations were significantly higher in MSG than in CTR rats. Additionally, reduced corticosterone clearance rate 9,10 and increased fasciculata to glomerolosa width ratio 11 have been reported in MSG rats.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…21 Conversely, circulating FB concentrations were significantly higher in MSG than in CTR rats. Additionally, reduced corticosterone clearance rate 9,10 and increased fasciculata to glomerolosa width ratio 11 have been reported in MSG rats.…”
Section: Discussionmentioning
confidence: 93%
“…2,3,4,6,7 Also, the changes in hypothalamic neuronal function particularly enhance hypothalamo-pituitary-adrenal (HPA) axis activity. [8][9][10][11][12] It is known that hypophagic, 13 MSG-damaged rats are characterized by increased adiposity and insulin resistance; 14 however, the exact mechanisms whereby these abnormalities develop are not fully understood. These MSG-induced changes in HPA axis activity, a key function for maintaining homeostasis, have been attributed to dysfunctions of several hypothalamic peptidergic and monoaminergic systems [15][16][17] driving pituitary function, and, in turn, modifying adrenal development and function, 11 thus resulting in enhanced corticoadrenal activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, as a consequence of prolonged hyperleptinemia [13] a down-regulation of adrenal Ob-Rb expression [26] takes place. This abnormality contributes with the characteristic corticoadrenal hyperactivity [34] and reduced clearance rate of glucocorticoid in MSG animals [35]. The adult phenotype in animals treated neonatally with MSG seems to be directly dependent on elevated corticosteroid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Increased proopiomelanocortin mRNA levels and adrenocorticotropic hormone concentration in the adenopituitary have been found in neonatal MSG-treated rats compared with controls (4 mg/g, 5 administrations intraperitoneally) (Skultetyova et al 1998). Furthermore, numerous studies have shown that neonates treated with MSG exhibited neuronal cell death with reduction of photoreceptor and glial cells (Blanks et al 1981, Reif-Lehrer et al 1975, Regan et al 1981, Hyndman and Adler 1981.…”
Section: Central Nervous Systemmentioning
confidence: 97%